Ethnoecology of Banjarese in Managing the Snakehead Fish in Barito River Basin and Tributaries - Krisdianto Krisdianto; Slamat Slamat; Pahmi Anshari; Oksi Ika Susilawati (Journal of Wetlands Environmental Management, 2021)
Historically, Banjarese is living in lowland around the Barito riverbank, in the southern part of Borneo Island, from about the 12th century. The first part of Banjarese history is a legend, but about the last three hundred years, there are data about Banjarese as a civilization with a kingdom involved in western colonialism history in Indonesia, as the pepper producer in the 17th century. They have settled almost in all Barito river tributaries and its basin and have been a part of the Barito freshwater wetland community, together with other Kalimantan ethnics such as Dayak hinterland or Malay in the coastal. This research aims to elucidate how far Banjarese is involved in managing wetlands, especially in managing snakehead's population, enjoying its benefit and sustainability. We observe the fishers' activity on the field and village along Barito River and its basin and tributaries, visit their villages and interview them, and collect data from forum group discussion. About 60 participative respondents involve in our research. They were interviewed about how to cat the fish, to evaluate ditches, or little ponds positioned lower than the land surface for placed sustainable fishes in a long dry season.Â  The result shows that Banjarese are traditionally managing the population of snakehead as a symbol of prosperity and conserve them for sustainability.